Changes in the live birth profile in Henan, China: A hospital registry‐based study. Issue 3 (20th February 2022) - Zhang, Xiaoli; Chen, Xi; Li, Bingbing; Xia, Lei; Zhang, Shan; Ding, Wenjun; Gao, Liang; Liu, Aiqing; Xu, Falin; Zhang, Ruili; Cui, Shihong; Wang, Xiaoyang; et al.
Abstract: Background: Preterm complications and neonatal asphyxia are the leading causes of death in those under 5 years of age. However, little information exists for the province of Henan, China. The purpose of this study was to explore changes in the live birth profile in a provincial hospital over the past 32 years in Henan, China. Methods: A retrospective analysis was conducted to reveal the characteristics of live neonates from 1987 to 2018. Results: There were 118 253 live births during the period, including 19 798 (16.74%) preterm births. The neonatal death rate was 6.45‰, and the top risk factor was preterm birth complications and birth asphyxia. Before 1998, neonatal death occurred primarily among term infants. Between 1999 and 2018, preterm infants, especially extreme and very preterm infants with very low birthweight, constituted more than half of all mortalities, and the preterm birth rate increased from 5.94% in 1999 to 16.69% in 2018. The risk factors associated with preterm birth were being male (aOR = 1.18, P  < 0.001), advanced maternal age (>35 years old; aOR = 1.08, P  = 0.008), gravidity ≥2 (aOR = 1.15, P  < 0.001), parity ≥2 (aOR = 1.50, P  < 0.001), placenta previa (aOR = 7.41, P  < 0.001), twin or multiple births (aOR = 10.63, P  < 0.001), hypertension (aOR = 2.08, P  < 0.001), and rupture of membrane (aOR = 5.03, P  < 0.001). Conclusions: The preterm birth rate has increased over the past 32 years from 4.98% to 16.69% in a provincial hospital in China. Preterm birth was the leading reason for neonatal death, and birth asphyxia was the major risk factor for death in term infants.